Personal Data Protection Regulations to Support Investment in Indonesia - Sumartono, Sumartono; Navalino, R Djoko Andreas; Wildan Akbar Hashemi Rafsanjani (HM Publisher, 2021)
Indonesia is a country that can be categorized as a big country when viewed from the aspect of population. The total population of Indonesia in 2019 is around 269 million, making Indonesia the fourth most populous country in the world. Indonesia is also the third largest owner of online transactions in Asia and one of the countries with the largest internet access in the world. However, Indonesia is one of the countries that does not have regulations that protect the personal data of its people even though with a very large number of people and potential, Indonesia should be able to reflect from Singapore, Malaysia, Thailand and even Laos. The importance of this regulation is because people are now in the era of Big Data. The research method used in this study is a descriptive qualitative research method with data and observations, with literacy studies as an addition. This research expects the government's ability to manage policies to protect the personal data of the Indonesian people so that there is no misuse of public data by irresponsible individuals.